How Can Digital Health Technologies Contribute to Sustainable Attainment of Universal Health Coverage in Africa? A Perspective - Olu, Olushayo; Muneene, Derrick; Bataringaya, Juliet Evelyn; Nahimana, Marie-Rosette; Ba, Housseynou; Turgeon, Yves; Karamagi, Humphrey Cyprian; Dovlo, Delanyo (Frontiers in Public Health, 2019)
Background: Innovative strategies such as digital health are needed to ensure attainment of the ambitious universal health coverage in Africa. However, their successful deployment on a wider scale faces several challenges on the continent. This article reviews the key benefits and challenges associated with the application of digital health for universal health coverage and propose a conceptual framework for its wide scale deployment in Africa. Discussion: Digital health has several benefits. These include; improving access to health care services especially for those in hard-to-reach areas, improvements in safety and quality of healthcare services and products, improved knowledge and access of health workers and communities to health information; cost savings and efficiencies in health services delivery; and improvements in access to the social, economic and environmental determinants of health, all of which could contribute to the attainment of universal health coverage. However, digital health deployment in Africa is constrained by challenges such as poor coordination of mushrooming pilot projects, weak health systems, lack of awareness and knowledge about digital health, poor infrastructure such as unstable power supply, poor internet connectivity and lack of interoperability of the numerous digital health systems. Contribution of digital health to attainment of universal health coverage requires the presence of elements such as resilient health system, communities and access to the social and economic determinants of health. Conclusion: Further evidence and a conceptual framework are needed for successful and sustainable deployment of digital health for universal health coverage in Africa.